2013
DOI: 10.5534/wjmh.2013.31.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Shock Wave Therapy and Its Application to Erectile Dysfunction

Abstract: Although phosphodiesterase type 5 inhibitors (PDE5Is) are a revolution in the treatment of erectile dysfunction (ED) and have been marketed since 1998, they cannot restore pathological changes in the penis. Low-energy shock wave therapy (LESWT) has been developed for treating ED, and clinical studies have shown that LESWT has the potential to affect PDE5I non-responders with ED with few adverse effects. Animal studies have shown that LESWT significantly improves penile hemodynamics and restores pathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 43 publications
(40 reference statements)
1
37
0
5
Order By: Relevance
“…Recent reports have indicated that low-intensity extracorporeal shockwave therapy (LiESWT) to the corpora cavernosa could play a role in penile rehabilitation [2,3]. Animal studies showed that LiESWT significantly improves penile haemodynamics and restores pathological changes in the penis of diabetic ED rat models [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have indicated that low-intensity extracorporeal shockwave therapy (LiESWT) to the corpora cavernosa could play a role in penile rehabilitation [2,3]. Animal studies showed that LiESWT significantly improves penile haemodynamics and restores pathological changes in the penis of diabetic ED rat models [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies showing that low-intensity linear shockwave treatment (LI-ESWT) is effective and successful in patients with ED due to vascular disorders, especially in those with arteriogenic ED (6,7,8). It is claimed that LI-ESWT causes neovascularization by stimulating angiogenesis and increases endothelial cell proliferation (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Estas ondas disparan una cadena de acontecimientos que lleva a la liberación de factores angiogénicos, que inducen nueva vascularización en los tejidos afectados y por consiguiente mejoran la circulación sanguínea. De aquí se derivó el uso de las ondas de choque de baja intensidad en el tratamiento de la DE, aplicando estas fuerzas de tensión a los cuerpos cavernosos con el fin de mejorar el flujo sanguíneo en el pene y la función endotelial mediante la estimulación de la angiogénesis (36). Esto se logra por la expresión de factores de crecimiento relacionados con la angiogénesis, tales como la óxido nítrico sintetasa endotelial (NOS), el factor de crecimiento endotelial vascular (VEGF, por su sigla en inglés) y factores de proliferación de células endoteliales, por ejemplo, el antígeno nuclear de proliferación celular.…”
Section: Ondas De Choque En El Tratamiento De La Disfunción Eréctilunclassified
“…Este proceso de nueva vascularización comienza a ser evidente en un lapso de cuatro semanas y persiste durante más de 12 semanas (7). Los efectos de las ondas de choque de baja intensidad consisten en la regeneración axonal (37), la reducción del estrés oxidativo y la inflamación (38), la mejora de las conexiones de capilares endoteliales (39), los cambios de la matriz de colágeno y el reclutamiento y la diferenciación de células madre o progenitoras (36).…”
Section: Ondas De Choque En El Tratamiento De La Disfunción Eréctilunclassified
See 1 more Smart Citation